KHK-A promotes fructose-dependent colorectal cancer liver metastasis by facilitating the phosphorylation and translocation of PKM2 - Chaofan Peng; Peng Yang; Dongsheng Zhang; Chi Jin; Wen Peng; Tuo Wang; Qingyang Sun; Zhihao Chen; Yifei Feng; Yueming Sun (Elsevier, 2024)
Excessive fructose diet is closely associated with colorectal cancer (CRC) progression. Nevertheless, fructose's specific function and precise mechanism in colorectal cancer liver metastasis (CRLM) is rarely known. Here, this study reported that the fructose absorbed by primary colorectal cancer could accelerate CRLM, and the expression of KHK-A, not KHK-C, in liver metastasis was higher than in paired primary tumors. Furthermore, KHK-A facilitated fructose-dependent CRLM in vitro and in vivo by phosphorylating PKM2 at Ser37. PKM2 phosphorylated by KHK-A inhibited its tetramer formation and pyruvic acid kinase activity but promoted the nuclear accumulation of PKM2. EMT and aerobic glycolysis activated by nuclear PKM2 enhance CRC cells' migration ability and anoikis resistance during CRLM progression. TEPP-46 treatment, targeting the phosphorylation of PKM2, inhibited the pro-metastatic effect of KHK-A. Besides, c-myc activated by nuclear PKM2 promotes alternative splicing of KHK-A, forming a positive feedback loop.